IMPLEMENTASI JARINGAN SENSOR NIRKABEL SEBAGAI BASIS SISTEM PERINGATAN DINI BAHAYA TANAH LONGSOR - Godlief Erwin Semuel Mige (Jurnal Media Elektro, 2012)
Landslide disaster frequency increasingly increases at rain season. This thing is because level of low vegetation at soil; land; ground contour that is steep relative. Besides there is no forewarning system attached at stall areas. At this research, Wireless Sensor Network (WSN)) designed to watch and detects the happening of landslide, by the way of reading vibration, either at surface or at landslide interior by using vibration censor (accelerometer), and can watch friction of surface of landslide with facility of Geographic Possition System (GPS) censor. Performance from network which has been tested to know quality of its the performance, then is done observation to consumption of current during the network works for watcher object, that is artificial landslide. Based on result of measurement and data analysis indicates that censor network nirkabel which has been built able to watch vibration activity of landslide with sensitivity 17%, and can read position of movement of surface of landslide with level of mistake 0.00014% only. In doing data communication one otherly, delay measurable maximum transmission is 1.275 seconds, and delay a minimum of 0.98 seconds. Then data package losing during 12 hours maximum measurement time equal to ± 2%, and consumption of current from WSN in watching landslide activity to reach resilience stripper of ±11 hours.